2006
DOI: 10.1111/j.1365-2885.2006.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

The complete analysis of oxytetracycline pharmacokinetics in farmed Pacific white shrimp (Litopenaeus vannamei)

Abstract: Lack of dosing information of the major antibiotics known as oxytetracycline (OTC) for the Pacific white shrimp (Litopenaeus vannamei) could have harmful impact on aquaculture in Thailand. The aim of this study was to detail complete pharmacokinetic information of OTC in the Pacific white shrimp. Sixty-four male L. vannamei weighing 14-22 g with carapace length of 2.30-3.00 cm in the standardized moulting stage of C-D(0) were used for the investigations. Single dose, 10 microg/g body weight OTC solution was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 13 publications
9
34
0
Order By: Relevance
“…Consequently, it is still difficult to deduce the factor affecting the type of model applicable. Calculated pharmacokinetic parameters of intra-sinus injection in the present study were in general agreement with those reported by Chiayvareesajja et al (2006) (Table 3). The distribution half-life of OTC in P. vannamei (0.21 h) was similar to that in P. monodon reported as 0.20 h (Uno et al 2006), while it is much shorter than that in P. japonicus Reed et al 2004).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Consequently, it is still difficult to deduce the factor affecting the type of model applicable. Calculated pharmacokinetic parameters of intra-sinus injection in the present study were in general agreement with those reported by Chiayvareesajja et al (2006) (Table 3). The distribution half-life of OTC in P. vannamei (0.21 h) was similar to that in P. monodon reported as 0.20 h (Uno et al 2006), while it is much shorter than that in P. japonicus Reed et al 2004).…”
Section: Discussionsupporting
confidence: 72%
“…Previous pharmacokinetic studies of OTC after intrasinus administration have been also analyzed by a two-compartment model in white shrimp (Penaeus (Litopenaeus) setiferus), kuruma shrimp (Penaeus (Marsupenaeus) japonicus) and P. monodon (Reed et al 2004;Sangrungruang et al 2004;Uno 2004;Uno et al 2006). In P. vannamei, the target species in this study, Chiayvareesajja et al (2006) have demonstrated both a two-and three-compartment models for OTC levels in hemolymph after intra-sinus dosing and made use of a two-compartment model for simplicity. On the other hand, Faroongsarng et al (2007) argued that OTC pharmacokinetics in shrimp may be modeled as a three-compartment system, including central (hemolymph), digestive (hepatopancreas) and peripheral compartments, rather than two.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytetracycline (OTC) is an antimicrobial drug widely used in intensive farming to treat enteric and respiratory diseases [1,2]. Due to oral administration and its pharmacokinetic, OTC dosage is in the range of g kg −1 medicated feeds and it is found in animal waste at concentrations of mg kg −1 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike vertebrates, for which metabolism and excretion of drugs take place in separate organs such as the liver and kidney, shrimp possess only a hepatopancreas, which plays several roles, such as collection, metabolism, and excretion of antibiotics [62]. Chiayvareesajja et al [63] proposed the hepatopancreas to be the major route for OTC elimination (60%) in whiteleg shrimp. There is little information on OTC content in the hepatopancreas possibly because of the complexity of the tissue, as stated by Reed et al [60].…”
Section: Antibiotic Residues In Penaeid Shrimpmentioning
confidence: 99%